Potential relationship between BK virus and renal cell carcinoma - Bulut, Yasemin; Ozdemir, Enver; Ozercan, Halil Ibrahim; Etem, Ebru Onalan; Aker, Fugen; Toraman, Zulal Asci; Firdolas, Fatih (Wiley-Blackwell, 2013)
The objective of the present study was to investigate the potential association between the presence of BK virus (BKV) DNA and mRNA and renal cell carcinoma and bladder transitional cell carcinoma. The formalin-fixed and paraffin-embedded tissue samples were obtained from 50 cancer patients with renal cell carcinoma, 40 cancer patients with bladder transitional cell carcinoma, 45 control patients with the benign renal pathology, and from another 25 control patients with benign bladder pathology. The samples were subjected to nested PCR for detection of BKV DNA and real-time reverse transcription PCR (real-time RT-PCR) for determining mRNA levels of BKV. The results of the nested PCR indicated that 23 (14.3%) of 160 samples were positive for BKV DNA. The relationship between the cancer and the presence of BKV DNA was significant (P<0.05). The BKV DNA positivity was significantly associated with the histological diagnosis of renal cell carcinoma (P=0.03), but not with that of bladder transitional cell carcinoma. The results of real-time RT-PCR showed that the mRNA of BKV VP1 was present in 69.5% of the BKV DNA positive samples. The levels of BKV mRNA were significantly higher in the renal cell cancer samples than in the control samples (P<0.05). The results of the present study confirm the association between BKV and renal cell cancer. The findings also indicated that the presence of BKV DNA resulted in a fivefold increase in the risk of development of renal cell carcinoma. J. Med. Virol. 85: 10851089, 2013. (c) 2013 Wiley Periodicals, Inc.
Keywords: BK virus; renal cell carcinoma; bladder transitional cell carcinoma